Perbandingan Metode Pelaksanaan Standar Konstruksi Jembatan Bailey dengan Pelaksanaan di Lapangan - Wiwik Listiowati; Agung Iswandi; Firmanilah Kamil (Teknik Sipil, Politeknik Negeri Ketapangg, 2022)
Bailey Bridge is a steel frame bridge that is generally used as a temporary emergency bridge. Although this type of bridge has been widely used, one of them is at the location of the Pesaguan-Kendawangan Road, but there are still some obstacles in the steel frame assembly process. Therefore, the researcher wants to make a comparison between the standard method of implementing the Bailey Bridge in the Temporary Bridge Technology book and the method implemented in the location. The purpose of this study was to determine the implementation method of bridge assembly at the location of Jalan PesaguanKendawangan and compare it with the standard method. The research was carried out using observation and interview methods with informants to obtain information about the assembly of the Bailey bridge at the location. The results of observations and interviews were analyzed by comparison with the standard Bailey Bridge. The data obtained shows that there are nine steps of implementing the assembly of Bailey Bridge components at the location of the PesaguanKendawangan Road Section, starting from the assembly of base plate components, panel components, panel post I components, transom components, pin components, bracing components, raker components, panel post II components, and finally the deck plate component. The comparison results show that 6 out of 10 bridge assembly parameters have met existing standards.